International airline alliances EC competition law/US antitrust law and international air transport - Lu, Angela Cheng-Jui (Kluwer Law International, 2003)
This new study takes a keen look at the problems facing the international community due to conflicts arising from applications of varying competition laws by different competition authorities to international airline alliances. As a result of privatisation, deregulation, liberalisation and globalisation, international air carriers form alliances with one another in order to cope with growing competition in the international air transport market. This book clearly provides an introduction to the background to and origin of airline alliances, different models of alliances and the related anti-competitive practices resulting from existing international airline alliances. The potential anti-competitive practices resulting from these cross-border alliances trigger a great deal of concern from various competition authorities. Thus, this study goes on to provide a detailed analysis regarding the relevant EC competition law and US antitrust law and their applications to alliance activities. The comparison of different applications of EC competition law and US antitrust law to international airline alliances provides leading research results first-hand. In the conclusion, the essential elements regarding establishing a level playing field in the international air transport market are identified and the author provides possible solutions for the harmonisation of different applications of competition law to international airline alliances